Reception of the legal idea in the creation and application of law - Malesa, Wojciech (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
Legal reasoning is an important element of drafting and applying law. It is done at several stages: 1) a debate during the legislative process; 2) reasoning of the entity applying the law; 3) a judicial discourse and 4) an academic assessment of judicial decisions. In drafting and applying law, the legislators, law users, judges and glossators touch upon a certain norm-creating concept. Following the Platonian concept, we can conclude that the concept is a certain idea which may be interpreted in several stages. With the example of a selected provision from the Act on the Relationship between the State and the Catholic Church in the Republic of Poland, the author of the paper indicates the role of legal reasoning in drafting and applying law at every stage. The most important thing is to interpret the ideal norm in a correct way and clearly draft it as a legal act. Correct performance of this procedure will facilitate further stages of applying the law.